Measuring and Analyzing the Effects of Economic Growth on Unemployment Rates in Iraq for (2003-2019) - خدر عبداللە, ئاكۆ; أحمد حمە, کامەران (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The main purpose of economic policies is not only to increase and expand production capacity, however, it also generally aims to provide and increase job opportunities through applying two related policies (ensure achieving sustainable economic growth and increasing the capacity of the national economy to absorb more employment). Unemployment is considered as one of the major economic and social problems that are considered as a threat to most of the economies in the world. From this point of view, this research tries to highlight the measurement and analysis of the impact of economic growth on unemployment rates in Iraq during the time span (2003-2019), to achieve the goal of the research, econometrics method has been used. Through applying time series Annual data. The results have showed the GDP at different levels has a one-way causal relationship with unemployment rates. This indicates the strong correlation between these two variables, furthermore, this result is consistent with the hypothesis of the research which states that the growth of GDP in Iraq has an impact on unemployment rates, a negative relationship between growth rates of GDP and unemployment rates has been achieved, that is the higher the growth rates (GDP) lead to Lower unemployment rates. The research suggests that the Iraqi government should direct oil revenues in favor of public and private investment focusing on development projects and public social services in order to reduce unemployment rates.